(untitled) (Philological Studies, 2019)
The article is focused on a ballad fairly widely distributed in Western Europe and known under various titles: The Hidden Death, Le Roi Renaud, Sir Oluf, Clerk Colvill, etc. The analysis seeks to determine its structural features, narrative types, semantic oppositions, characters, gender perspective, structural analogues in the South Slavic tradition, its overall meaning and consider certain aspects of ballad poetics in the context of comparative studies.